2022
DOI: 10.3390/ijerph191610320
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Accidents Caused by the Use of Smartphone by Pedestrians Are Task- and Environment-Dependent

Abstract: Using smartphones during a task that requires an upright posture can be detrimental for the overall motor performance. The aim of this study was to determine the risks of accidents caused by the use of smartphones by pedestrians while walking in a controlled (laboratory) and a non-controlled (public street) environment. Two hundred and one participants, 100 men and 101 women, all young adults, were submitted to walking activities while texting messages and talking on the phone. The risk of accident was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The problematic use of the above-mentioned technologies may also contribute to the legal consequences related to improper compliance with the law in the internet sphere. The research results also emphasize the correlation between the risky use of smartphones and the creation of dangers in the public environment, especially among pedestrians staring at the smartphone screen [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The problematic use of the above-mentioned technologies may also contribute to the legal consequences related to improper compliance with the law in the internet sphere. The research results also emphasize the correlation between the risky use of smartphones and the creation of dangers in the public environment, especially among pedestrians staring at the smartphone screen [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies that have assessed postural control in a quiet standing position while simultaneously performing tasks with a smartphone have shown decreased motor performance; consequently, postural stability deteriorated [9][10][11], which can contribute to the risk of injuries or falls. Moreover, previous studies have reported physical and psychological problems due to smartphone use [12,13] and increased pedestrian injury risk [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other age cohorts, individuals under the age of 35 years make more emergency calls owing to mishaps resulting from smartphone use while walking. The annual incidence of hospital admissions for young individuals has shown a consistent upward trend [ 7 , 8 ]. Furthermore, statistical data revealed that a significant proportion (80%) of accidents occurred within traffic facilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%